Improving Marketing Performance Through Competitive Advantage in Phase Two Of The Covid-19 Pandemic - Maulana Ichsan; Naili Farida; Sari Listyorini (Fakultas Pariwisata dan Perhotelan Universitas Negeri Padang, 2022)
The marketing performance of small and medium businesses in the Ancol tourism area is influenced by an effective market strategy so that they are able to realize a competitive advantage. The purpose of this study is to examine market strategies in competitive advantage, and their implications for marketing performance in small and medium businesses in the Ancol tourism area. The sample research technique uses Probability Sampling. The sample selection technique in this study used Proportional Random Sampling with the sample in this study amounting to 235 small and medium businesses in the Ancol area during the Covid-19 pandemic from 70 small and medium businesses with a scale of 1 to 10 questionnaires to find out the interpretation of market strategies, competitive advantage, and marketing performance. The data technique was analyzed using multiple linear regression with the intervening test. Research statement: